The structure of and origin of nodular chromite from the Troodos ophiolite, Cyprus, revealed using high-resolution X-ray computed tomography and electron backscatter diffraction - Prichard, H.; Barnes, S.; Godel, B.; Reddy, Steven; Vukmanovic, Zoja; Halfpenny, Angela; Neary, C.; Fisher, P. (Elsevier BV, 2015)
Nodular chromite is a characteristic feature of ophiolitic podiform chromitite and there has been much debate about how it forms. Nodular chromite from the Troodos ophiolite in Cyprus is unusual in that it contains skeletal crystals enclosed within the centres of the nodules and interstitial to them. 3D imaging and electron backscatter diffraction have shown that the skeletal crystals within the nodules are single crystals that are surrounded by a rim of polycrystalline chromite. 3D analysis reveals that the skeletal crystals are partially or completely formed cage or hopper structures elongated along the <111> axis. The rim is composed of a patchwork of chromite grains that are truncated on the outer edge of the rim. The skeletal crystals formed first from a magma supersaturated in chromite and silicate minerals crystallised from melt trapped between the chromite skeletal crystal blades as they grew. The formation of skeletal crystals was followed by a crystallisation event which formed a silicate-poor rim of chromite grains around the skeletal crystals. These crystals show a weak preferred orientation related to the orientation of the core skeletal crystal implying that they formed by nucleation and growth on this core, and did not form by random mechanical aggregation. Patches of equilibrium adcumulate textures within the rim attest to in situ development of such textures. The nodules were subsequently exposed to chromite under-saturated magma resulting in dissolution, recorded by truncated grain boundaries in the rim and a smooth outer surface to the nodule. None of these stages of formation require a turbulent magma. Lastly the nodules impinged on each other causing local deformation at points of contact.